Classifications, Surface Characterization and Standardization of Nanobiomaterials - Ali, Salah H. R.; Almaatoq, Marwah M.; Mohamed, Abdalla S.A. (International Journal of Engineering and Technology, 2013)
Biomaterials measurement and standardization are necessary for suitable use in medical industries. Nanobiomaterials used in living creature body, taking in account of their biocompatibility, nontoxic and non carcinogenic. These requirements are eliminate many engineering materials that are available. Thus, the nanobiomaterial should possess adequate physical and mechanical properties and surface characteristics to serve as augmentation or replacement of body tissues. This paper discusses classification of different biomaterials and their standards reference in micro- and nano-scale are used in medical engineering applications in details.